A farnesoic acid‐responsive transcription factor, Hot1, regulates yeast‐hypha morphogenesis in Candida albicans. Issue 9 (10th April 2017) - Ahn, Chan‐Hong; Lee, Sohyoung; Cho, Eunji; Kim, Heegyu; Chung, Beomkoo; Park, Wanki; Shin, Jongheon; Oh, Ki‐Bong
Abstract : Candida albicans hyphal formation is inhibited by a quorum‐sensing molecule, farnesoic acid, which accumulates in the medium as the cells proliferate. We recently showed that Pho81 is essential for the inhibition of hyphal growth by farnesoic acid. Here, we describe a newly identified regulator, Hot1, which increases the expression of PHO81 . The binding site of Hot1 in the PHO81 promoter region was identified by DNase I protection assay. The hot1 Δ mutant grows extensively as filaments. Furthermore, the inhibition of hyphal formation and the repression of major signaling pathway components in response to farnesoic acid are defective in hot1 Δ mutant cells. These data suggest an important role for HOT1 in the inhibition of hyphal development by farnesoic acid in this fungus. Abstract :